From Tolerance Modeling to Exact Description of Heat Conduction in Biperiodic Composites - WIERZBICKI, Ewaryst; MAZEWSKA, Marta (Engineering Transactions, 2015)
In the paper we study the temperature boundary effect behavior in the dividing wall made of a composite conductor in which every area parallel to the outside and the inside plane areas has identical biperiodic structure. The proposed modeling approach is restricted to the hexagonal case of bi-periodicity in which the hexagonal cell can be divided onto three rhombus parts with different thermal properties. Considerations deal with anisotropic conductors.